2015
DOI: 10.1371/journal.pone.0133823
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and In Vitro Cytotoxicity of Essential Oils from Leaves and Flowers of Callistemon citrinus from Western Himalayas

Abstract: BackgroundPlant-based traditional system of medicine continues to play an important role in healthcare. In order to find new potent source of bioactive molecules, we studied the cytotoxic activity of the essential oils from the flowers and leaves of Callistemon citrinus. This is the first report on anticancer potential of essential oils of C. citrinus.MethodsCytotoxicity of essential oil was evaluated using sulfo-rhodamine B (SRB) assay against human lung carcinoma (A549), rat glioma (C-6), human colon cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
2
37
0
1
Order By: Relevance
“…As in other studies, we also find that women are more vulnerable to the economic impacts of health expenditures, but greater income and household size protect against health-related impoverishment. 28,40 Previous studies have estimated that between 3.2% and 3.8% of the population in India fell into poverty as a result of health care payments. 9,26,41 Our estimate for 2014, which uses more recent data, is that 2% of the population became impoverished due to health spending.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other studies, we also find that women are more vulnerable to the economic impacts of health expenditures, but greater income and household size protect against health-related impoverishment. 28,40 Previous studies have estimated that between 3.2% and 3.8% of the population in India fell into poverty as a result of health care payments. 9,26,41 Our estimate for 2014, which uses more recent data, is that 2% of the population became impoverished due to health spending.…”
Section: Discussionmentioning
confidence: 99%
“…This work contributes to a growing literature on the economic implications of health expenditures in India among older age groups. 11,22,28,29 2 | METHODS…”
mentioning
confidence: 99%
“…15240‐062, Invitrogen Biosciences, India). Cells were incubated at 37 °C in a 5% CO 2 having 95% relative humidity in CO 2 incubator …”
Section: Methodsmentioning
confidence: 99%
“…The lavender essential oil extracted from Lavandula angustifolia contains high percentages of linalool and linalyl acetate, which induce apoptosis and the arrest at G2/M phase of cell cycle in PC3 and DU145 prostate cancer cells [61]. Kumar and coworkers [62] have demonstrated that the essential oils from leaves and flowers of Callistemon citrinus inhibit cell cycle progression at S and G2/M phases in human lung carcinoma (A549) and rat glioma (C-6) cells. In addition, the Asteraceae Artemisia campestris and Artemisia herba-alba essential oils effectively kill Leishmania promastigotes by apoptosis and halting cell cycle at G0/G1 stage [48].…”
Section: Discussionmentioning
confidence: 99%